Program Keluarga Harapan (PKH) dan Upaya Pemerintah Mengentaskan Kemiskinan di Kelurahan Sidorejo Hilir, Medan Tembung - Panjaitan, Hulman; Desinta Desinta; Bago, Rhyfka Arlina; Sinurat, Yohana; Tamba, Josua Armando; Julia Ivana (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study investigates the implementation of the Family Hope Programme (PKH) in Sidorejo Hilir Sub-district, Medan Tembung District, Medan City, as part of the government’s efforts to reduce poverty. The study focuses on the methods used to implement the PKH, the constraints and difficulties encountered during its implementation, and how the programme has impacted the socio-economic conditions of beneficiary families. This research employs a descriptive qualitative approach to collect data through interviews, observations, and documentation with village officials, PKH facilitators, and Beneficiary Families (KPM). The research findings indicate that the implementation mechanism of the PKH in Sidorejo Hilir Sub-district has followed the procedures for data collection via the DTKS, verification, selection of beneficiary families, and the provision of assistance on a regular basis, as well as fulfilling responsibilities in the fields of education and health. The PKH has been shown to reduce the expenditure burden on poor families, improve access to education and health care, and encourage behavioural changes that foster greater awareness of the importance of education and health. However, the programme still faces a number of challenges. These include inaccurate beneficiary data, delays in disbursement, a limited number of field officers, and a lack of public understanding of the programme’s mechanisms and responsibilities. Overall, the PKH has made a positive contribution to poverty alleviation in Sidorejo Hilir. However, to achieve sustainable poverty alleviation, improvements are needed in data collection, coordination, support, and economic empowerment.